Sustainable Preservation of Plant-Based Meat Analogues Using Distinct Conifer Needle Aqueous Extracts - Gaižauskaitė, Žydrūnė; Černauskas, Darius; Zabulionė, Aelita; Trakšelė, Lina; Korpinen, Risto; Almonaitytė, Karolina (MDPI, 2026)
The increasing demand for sustainable and clean-label foods has intensified the search for natural preservatives that are capable of replacing synthetic additives. In this study, an exploratory assessment of two distinct spruce needle aqueous extracts were conducted—an aqueous extract of Picea pungens (NWE-1) and an aqueous extract of Picea abies obtained after prior supercritical CO2 treatment (NWE-2)—and both were investigated as potential bioactive ingredients for plant-based meat analogues. Using UPLC–MS, both extracts were comprehensively characterized, revealing a diverse array of phenolic acids, flavonoids, and glycosides. Even though NWE-2 contained a broader range of bioactive compounds, NWE-1 exhibited superior antibacterial performance (total microbial count (TMC)—4.94 log CFU/g), effectively limiting microbial contamination and ensuring product stability for up to 16 days of storage below the typical spoilage threshold (6.0–7.0 log CFU/g). Sensory analysis indicated that the model plant-based meat analogue matrix tolerated up to 3% (w/w) inclusion of NWE-1 and 5% (w/w) inclusion of NWE-2 before significant degradation of flavor and overall acceptability occurred. By utilizing conifer needles as an underexploited side-stream biomass, this work offers an approach for the valorization of conifer needle material through combined green extraction and food application, contributing to circular and resource-efficient processing concepts. The study provides an exploratory perspective on the potential role of forest-derived resources in the development of natural preservatives and their possible contribution to more sustainable food preservation strategies within a circular bioeconomy framework.
Keywords: bioactive compounds; biomass valorization; clean-label preservation; functional food ingredients; green extraction; natural preservatives; resource-efficient processing; sustainable extraction; upcycled ingredients